EFICIÊNCIA DA MANIPUEIRA NO CONTROLE DO ÃCARO-BRANCO DO MAMOEIRO (NOTA PRÉVIA) - Ponte, J. Júlio da (REVISTA DE AGRICULTURA, 2015)
EFICIÊNCIA DA MANIPUEIRA NO CONTROLE DO ÃCARO-BRANCO DO MAMOEIRO (NOTA PRÉVIA)